Highlights on Drug and Ion Release and Recharge Capacity of Antimicrobial Removable Prostheses - Abualsaud, Reem; Gad, Mohammed M. (European Journal of Dentistry, 2022)
This article aimed to review the ion and drug release, recharge abilities, and antimicrobial properties of drug/ion-releasing removable prostheses, and to assess their capability in preventing and inhibiting denture stomatitis as well preventing caries and reversing carious lesions. Data was collected from published scientific papers listed in PubMed database from January 1975 to December 2021. English full-text articles, involving clinical or in vitro studies, focusing on removable prostheses and are concerned with drug/ion release and rechargeability as a way to prevent or inhibit denture stomatitis or dental caries were included. The relevant articles reported that ion- or drug-modified polymethylmethacrylate acts as a reservoir for these ions and drugs and is capable of releasing significant amounts with sustained release effect. Recharging of modified resin resulted in greater sustainability of ion and drug release, thus improving the long-term effects of protection against demineralization and reducing the adhesion of Streptococcus mutans and Candida albicans. Modifications of removable prostheses with rechargeable ions and drugs enhance remineralization, hinder demineralization, and reduce microbial adhesion in difficult-to-access areas. Selection of denture base for clinical use will consider its ability to act as an ion/drug reservoir that is capable of release and recharge.
Keywords: removable dental prostheses; PMMA; candidiasis; mineralization; recharge; dental caries; fluoride release; caries prevention; antimicrobial effect; denture stomatitis